EFFECT OF POTASH FERTILIZERZATION ON WHEAT PRODUCTIVITY UNDER INTEGRAL IRRIGATION SYSTAM - Mahamed Ali Gamal (Mesopotamia Journal of Agriculture)
Wheat of Triticum aestivum was planted in four agricultural fields in Neniva governerate classified as Aridsol .The experiment of split different locations plot design was implemented to random complete block design RCBD included two treatment potash fertilizers mixed with soil (0 and 20) as potassium sulfate /donum for 600 donum area for each replicate the potash fertilizer was added to the soil in two doses the first dose .was mixed with the soil in planting the second dose was after branding stage the nitrogen fertilizer was added to the soil in a rate of 200 kg N/ha as 130 kg/ha in the planting and the rest was sprayed seven doses with integral irrigation the phosphorous was added in a rate of 120kg/ha as a triple super phosphate in on dose before planting mixed with area .The results revealed to the presence of significant urinations in growth appearance (plant length, weight of 1000 grain , the grain number in the spike , a grain weight /spike ,spike number , total yield and grain protein content